A qualitative study exploring experiences of racial minority stress in pharmacy education and practice - Arisha Ahmed; Michael Hagos; Immer Bhatti; Nia Cartwright; Orieoma Chukwu-Etu; Angela Burini; Lola Dabiri; Clare Tolley; Charlotte Lucy Richardson; Amandeep Doll; Tanya Miah; Adam Pattison Rathbone (Elsevier, 2024)
Background: Despite 49.1% of registered pharmacists in the UK being from a Black, Asian and Minority Ethnic (BAME) background, senior management roles within pharmacy are dominated by white males. People from BAME communities may experience minority stress which contributes to a professional attainment gap compared with non-BAME colleagues. Minority stress describes additional stressors, such as unconscious bias, micro-aggression and racial minority stress, experienced by minoritized people to adhere to the social norms of the majority. There is little evidence describing experiences of minority stress in pharmacy practice and education. The aim was to explore experiences of racial minority stress in pharmacy education and practice. Methods: A convenience sample of pharmacy students and pharmacists were recruited via email and social media posts to volunteer to take part in interviews and focus groups. A topic guide was used to explore experiences of unconscious bias, microaggressions and racial minority stress in education and practice. Interviews and focus groups were transcribed verbatim and inductively analysed using thematic analysis underpinned by a phenomenological approach. Ethical approval was granted from Newcastle University (5340/2020, 2430/2593). Results: Forty-five participants were recruited. Six focus groups and sixteen one-to-one semi-structured interviews were conducted. The sample was varied, with 56% (n = 25) students and 33% (n = 15) registered pharmacists from community, hospital, primary care, academia and an additional 11% (n = 5) still in foundation training in these sectors. The sample include diversity of racial identities, including 40% (n = 18) South Asian, 27% (n = 12) White, 15% (n = 7) Black, 7% (n = 3) Chinese and Arab mixed, 2% (n = 1) and 2% (n = 1) Not disclosed. Three themes were identified - Theme 1) Experiences of racial minority stress, Theme 2) Making sense of racial minority stress, and Theme 3) Responding to racial minority stress. Participants characteristics (for example skin colour, dialect, religious dress) made them feel susceptible to judgement, racist comments and microaggressions in education and practice. Participants required time to interpret, understand and make sense of incidents of racial minority stress. Responses to stressors included 'ignoring ignorance' and using a 'professional identity' to mask feelings. However, malicious comments and actions from other pharmacy staff were responded to differently to experiences from patients. Participants reported poor self-confidence to challenge racist behaviours in the workplace. Conclusions: The aim of this study was to explore experiences of racial minority stress in pharmacy education and practice. This study shows dealing with microaggression, racial minority stress and judgement in pharmacy education and practice is a burden experienced by people from BAME backgrounds. These experiences could contribute to the professional attainment gap in pharmacy, as making sense of these experiences is an additional burden pharmacists and trainees must bear in comparison to people from non-BAME backgrounds. Further work is needed to explore interventions to reduce minority stress in pharmacy practice and education to reduce the attainment gap across the sector.